2014
DOI: 10.1097/nen.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in Early Markers of Muscle Involvement Support a Delay in Myogenesis in Spinal Muscular Atrophy

Abstract: Spinal muscular atrophy (SMA) is characterized by loss of motor neurons in the spinal cord that results in muscle denervation and profound weakness in affected patients. We sought evidence for primary muscle involvement in the disease during human development by analyzing the expression of several muscle cytoskeletal components (i.e. slow, fast, and developmental myosin, desmin, and vimentin) in fetal or postnatal skeletal muscle samples from 5 SMA cases and 6 controls. At 14 weeks' gestation, SMA samples had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Observations by different authors suggested that the myogenic program is deregulated in SMA mice models, 34 human myoblasts, 35 and postnatal muscle samples 18 from patients with SMA. We quantified expression levels of 3 myogenic regulatory factors, namely, myoblast determination 1 (MYOD), myogenin (MYOG), and the muscle-specific myogenic factor 5 (MYF5) in SMA-I samples (n = 3) and age-matched controls (n = 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations by different authors suggested that the myogenic program is deregulated in SMA mice models, 34 human myoblasts, 35 and postnatal muscle samples 18 from patients with SMA. We quantified expression levels of 3 myogenic regulatory factors, namely, myoblast determination 1 (MYOD), myogenin (MYOG), and the muscle-specific myogenic factor 5 (MYF5) in SMA-I samples (n = 3) and age-matched controls (n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…38 Recent investigations have demonstrated that SMN has a role in myogenesis and that normal muscle differentiation requires adequate levels of SMN 34,35 ; these considerations support the hypothesis that a delay in muscle maturation is one of the primary pathologic components of SMA. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, immature appearing proximal axons and dorsal root ganglia have been identified. Collectively, this suggests an element of developmental arrest in SMN deficient nerve and muscle and suggests that SMA is not purely a progressive neurodegenerative process [13]. Polyneuronal innervation of muscle in the early post-natal mouse differs from that in the human where one axon probably innervates one muscle fibre at birth.…”
Section: Human Pathology In Sma Typementioning
confidence: 99%
“…For example, acute satellite cell proliferation has been reported in response to spinal muscular atrophy-induced muscle denervation (Martinez-Hernandez et al, 2014) presumably as an attempt to increase the nuclear population for elevating transcriptional signaling, yet, the atrophy signaling predominates the muscle, and the net result is that denervated muscles become smaller, even with an acute increase in satellite cells. Thus, effective strategies to combat sarcopenia and accelerated muscle loss in aging should evaluate the effects of interventions on both proliferation and differentiation of satellite cells and their daughter cells.…”
Section: Modulators Of Satellite Cells In Sarcopeniamentioning
confidence: 99%